Shaman Representations in the Painted Cave at Sarawak, Malaysia - Junior Kimwah (ISVS Journal Secretariat, 2023)
An anthropomorphic image is a very significant image in the development of a society, especially in terms of the socio-cultural aspects and early beliefs of that society. In this context, the figurative images produced on the walls of the Painted Cave, Sarawak can be considered as a representation of the ‘shamans’. The Painted Cave was believed to have been used by the prehistoric people at that time as a burial site. A shaman is believed to have acted as the head of the ritual and had led the community at that time in conducting the death ceremony. The objective of this research is to understand the physical features that clearly show this figurative image as a shaman’s image. Based on the appearance and the shape of the images produced, this research identified several shaman images found on the cave walls through observations during fieldwork and numbers of images taken using photography. The paper concludes that the Painted Cave has been a holy place for the people who had lived in the cave because the site houses several boat coffins that play a big role in the death ceremony. The Shaman had acted to accompany the spirit of the deceased to the realm of death by holding a ceremony in the cave. The results of the study prove the existence of the shamanic practices and the early beliefs of prehistoric societies in the Painted Cave. These practices have lasted for several centuries.